ChemInform Abstract: Silver‐Catalyzed Cascade Reaction of Tosylmethyl Isocyanide (TosMIC) with Propargylic Alcohols to (E)‐Vinyl Sulfones: Dual Roles of TosMIC. Issue 50 (December 2015) - Bounar, Haniya; Liu, Zhenhua; Zhang, Lin; Guan, Xiaoxue; Yang, Zonglian; Liao, Peiqiu; Bi, Xihe; Li, Xingqi
Abstract: The first examples where TosMIC (II) acts as both an allenylative reagent and sulfonyl source in a cascade reaction are presented.